Pengaruh Brand Image dan Kualitas Layanan terhadap Kepuasan Pengguna Gojek (Studi pada mahasiswa Manajemen S1 Universitas Bandar Lampung) - Anisa Faradila; Iskandar Ali Alam (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to examine the effect of brand image and service quality on Gojek user satisfaction among undergraduate students of the Management Study Program at Universitas Bandar Lampung. A quantitative research approach was employed using a survey method with Likert-scale questionnaires distributed to 76 respondents who had used Gojek services. The collected data were analyzed using multiple linear regression to assess the influence of brand image and service quality on user satisfaction. Data analysis included validity tests, reliability tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The results indicate that brand image and service quality have a positive and statistically significant effect on user satisfaction, both partially and simultaneously (p < 0.05). Service quality shows a more dominant influence compared to brand image in enhancing user satisfaction. The coefficient of determination indicates that variations in user satisfaction can be substantially explained by the two independent variables. Although the level of user satisfaction is relatively high, continuous improvements in service consistency, timeliness, and reliability are required to maintain sustainable user satisfaction. This study highlights the importance of strengthening brand image and improving service quality as key strategies to enhance Gojek user satisfaction, particularly among the student segment.